Pengembangan Materi Ajar Teks Prosedur Bermuatan Kearifan Lokal Simalungun Berbantuan Web Google Sites Untuk Siswa Kelas VII SMP - Fania Nurtriana; Achmad Yuhdi (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2024)
This research aims to, (1) describe the process of developing procedural text teaching materials containing local wisdom using the Google Sites website, (2) describe the form of developing procedural text teaching materials containing local wisdom in Simalungun using the Google Sites website, and (3) describe the feasibility of teaching materials procedure text containing local Simalungun wisdom with the help of the Google Sites website. The development of procedural text teaching materials containing Simalungun local wisdom with the help of the Google Sites website uses the ADDIE model which is limited to only going through the analysis, design and development stages. The validation stage involved material expert lecturers, media expert lecturers and two Indonesian language teachers. The sample for this research was 31 class VII students at SMP Negeri 2 Siantar using the Purposive Sample technique. Data collection techniques were interviews and questionnaires. The research instrument was a validation questionnaire sheet for material experts and media experts using Likert scale calculations. Data analysis uses qualitative descriptive analysis. The results of the research show that the product of procedural text teaching materials containing Simalungun local wisdom with the help of the Google Sites website received the "Very Good" criteria with an average of 88.85%, with results from material experts of 83.41% with the "Very Good" criteria. The results from media experts were 88% with the criteria "Very Good" and Indonesian language teachers 92% and 90%, so that the teaching materials were suitable for use as supporting teaching materials in the learning process.